Cheirocystis liexiensis, a new rhombiferan blastozoan (Echinodermata) from Lower Ordovician of South China Block - Liu, Qi; Paul, Christopher R.C.; Mao, Ying-Yan; Li, Yue; Fang, Xiang; Huang, Di-Ying (Palaeoworld, 2024)
Rhombiferan (Echinoderm) fossils from the Lower Ordovician Liexi fauna in the South China Block are identified as Cheirocystis liexiensis n. sp. Details of the stem, theca and brachioles are preserved. Cheirocystis liexiensis is characterized by plates with single axial ridges and outer proximal stem ossicles with two smooth annular flanges, the lower curved downwards. The earliest Cheirocrinidae in the South China Block was from the Tremadocian in Jiangnan Slope, then migrated to the margin of Jiangnan Slope during Floian, and finally to the intra-platform during Middle–Upper Ordovician. Spatial-temporal distribution of the cheirocrinid fossils throughout the Lower to Upper Ordovician units in the South China suggests probably a slow westward biogeographic migration of cheirocrinids. Newly discovered Lagerstätten, such as the Liexi fauna, allow tests of geographical bias in our knowledge of the fossil record. Such testing should become routine.